180k views
5 votes
the sum of two polynomials 10a2b2 – 8a2b + 6ab2 – 4ab + 2. If one addend is –5a2b2 + 12a2b – 5, what is the other addend?

1 Answer

5 votes

Answer:


15a^2b^2-20a^2b+6ab^2-4ab+7

Explanation:

Given,

Sum of two polynomial =
10a^2b^2 - 8a^2b + 6ab^2 - 4ab + 2

One addend =
-5a^2b^2 + 12a^2b - 5

Let x be the other addend,


\implies x + (-5a^2b^2 + 12a^2b - 5)=10a^2b^2 - 8a^2b + 6ab^2 - 4ab + 2


\implies x = 10a^2b^2 - 8a^2b + 6ab^2 - 4ab + 2-(-5a^2b^2 + 12a^2b - 5)


\implies x = 10a^2b^2 - 8a^2b + 6ab^2 - 4ab + 2+5a^2b^2 - 12a^2b + 5

Combine like terms,


x=15a^2b^2-20a^2b+6ab^2-4ab+7

Hence, other addend is
15a^2b^2-20a^2b+6ab^2-4ab+7

User Romain Rastel
by
4.3k points